Power and communication in the Participatory Upland Development Program in the Dampalit Watershed of the Makiling Forest Reserve (MFR), Philippines - Moscoso, Mildred O.; Cadiz, Maria Celeste H.; Flor, Alexander G.; Torres, Cleofe S.; Cardenas, Virginia R. (2014)
This case study sought to explore and understand the relationship of power and communication in the Participatory Upland Development Program in the Dampalit Watershed of the Makiling Forest Reserve (Dampalit Program). Premised at the assumption that communication is interaction, it: 1)described the context of the interaction between SAMALUP farmers and the MCME implementers in the Dampalit Program; 2)identified the different stage of their interaction; 3)identified the strategies they employed in the interaction; 4)surfaced the relations power embedded in their interaction; and 5)interpreted the relationship of power and communication in program. Primary and secondary data were gathered where the primary data consisted of interviews with nine of the actors. Data went through coding, surfacing of themes, and then thorough interpretation and critique. MCME-SAMALUP interaction proceeded in four stages where MCME was generally the dominant actor throughout the interaction with SAMALUP. Its "powe over" SAMALUP came from expertise, legitimacy, and coercion. In the beginning SAMALUP went through individual and organizational empowerment and developed "power within", "power to", and "power with" through various MCME initiated activities. The partnership formed between the two actors continued until after the program and was characterized by a common goal; it was relational; it provided sense of legitimacy to SAMALUP; and; it was based on unequal power relationship. The communication processes that helped in the empowering SAMALUP were compromise, capability building and organizational development, and the development of interpersonal relationships. On the other hand, communication processes that have undermined SAMALUP's ability to be empowered were inclusionary control, governmentality, and normalization.